ANALISIS UPAYA DAN PERAN PERLINDUNGAN HUKUM TERHADAP KASUS PERETASAN DATA BANK SYARIAH INDONESIA - Keliat, Venia Utami; Siregar, Andini Pratiwi; Zulkifli, Suhaila; Purba, Iin (Ilmu Hukum Prima (IHP), 2023)
The development of information and communication technology has had a significant impact on various sectors of life, including the banking sector. The legal system has made essential safeguards to protect bank and customer data security. The latest information regarding developments in the Indonesian Kapital data leak case must be sought through trusted news sources or contacting authorities such as the OJK or Bank Indonesia to obtain accurate and up-to-date information. The Consumer Protection Law seeks to protect bank customers by limiting standard clauses that cannot be avoided in today's banking business world. The method in this research uses normative legal research. Issues that occur in the banking world relate to the legal position of banking in cases of leakage of Indonesian Sharia Bank customer data and banking legal protection efforts that have been carried out by the legal system to protect the security of bank data and customer data. There are two factors that cause leaks of customer personal data, namely internal and external factors. Cases of customer data leakage are serious violations of privacy and information security. Banks, including Islamic banks, have a big responsibility in maintaining the confidentiality of customer data and protecting their personal information. If a data leak occurs, the bank could face legal and regulatory consequences, and could potentially harm their reputation. The method in this research uses normative legal research.